(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the treatment outcomes of fingertip amputations using the occlusive dressing method at Thu Duc City Hospital. Research Method: Descriptive case series. A total of 26 cases with 31 fingertip amputations were successfully treated and included in the study; 9 cases were excluded due to insufficient information, and 10 cases dropped out of treatment. Conclusion: The median wound healing time was 6 weeks, with a median two-point discrimination test value of 4mm. All cases achieved full re-epithelialization. The median additional nail bed length was 3mm. The nail bed length growth in P3 and P4 groups was statistically significantly greater than in P6 and P7 groups (p = 0.008). Similarly, nail bed length growth in N5 and N6 groups was statistically significantly greater than in other types (p = 0.025). 90% of cases had functional recovery according to the DASH score, allowing them to resume work after 3 months of treatment. Patients with B8 fingertip bone injuries were statistically significantly less likely to recover hand function compared to other types (p = 0.018).